ROLE OF ENDOGENIC INTOXICATION IN MUSCLE INJURY IN EXPERIMENT - Dzhyvak, V. H.; Khlibovska, O. I.; Klishch, I. M. (International Journal of Medicine and Medical Research, 2020)
Background. Endogenous intoxication is a multicomponent complex process due to the endogenous biological products or dysfunction of systemic natural detoxification. Objective. The aim of the research was to study the dynamics of indices of endogenous intoxication in rats with traumatic muscle damage in the experiment. Methods. The experiment was performed on 45 non-linear white rats, which were modeled with traumatic muscle damage. The level of endogenous intoxication was assessed by the content of medium plasma molecules (MMM), leukocyte and erythrocytic index of intoxication (LII and EII). The research was conducted on the 1st, 3rd, 7th, 14th days after the injury. Results. It was found that traumatic muscle damage causes endotoxemia. Manifestations of endogenous intoxication are: the increase of MMM1 in 2.3 times, MMM2 in 2.8 times compare to the intact animals. The level of this indicator slightly decreased in 7 days. Simultaneously with an increase in the MCT level in the post-traumatic period, the total toxic effect on the erythrocyte membrane also increased, which was manifested by a significant increase in EII in all terms of observation. Conclusions. Traumatic damage of the muscles is accompanied by the growth of molecules of average mass in upto 7 days of observation, which significantly differ from the indicators of the intact group. The results of our research prove that traumatic muscle damage causes endotoxicosis development evidenced by accumulation of endotoxins in the animals’ body that is proved by significant changes in endogenous intoxication indices: i.e. erythrocytic and leukocytic indexes of intoxication and content of medium mass molecules.